Navigating Industry 4.0: The Strategic Role of Dynamic Capabilities in Transforming Indonesian Manufacturing - Wahyudi, Novan; Arviansyah, Arviansyah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Incorporating industry 4.0 technologies into manufacturing operations is hindered by significant organizational and managerial challenges. This research addresses the problem of insufficient organizational and managerial strategies in embracing industry 4.0 within Indonesian manufacturing companies. Utilizing a quantitative approach, data was collected through a survey distributed among Indonesian manufacturers. The collected data was analyzed using PLS-SEM to identify the critical factors influencing successful Industry 4.0 integration. The findings highlight the critical role of dynamic capabilities – sensing, seizing, and reconfiguring – in enhancing Industry 4.0 capabilities. By fostering these dynamic capabilities, companies can effectively integrate Industry 4.0 technologies, leading to increased competitiveness and operational efficiency within the Indonesian manufacturing sector. This study offers valuable insights for managers and policymakers as they navigate the challenges of Industry 4.0 and build a robust manufacturing ecosystem in Indonesia.